2020
DOI: 10.1186/s13052-020-0806-8
|View full text |Cite
|
Sign up to set email alerts
|

A case series of CHARGE syndrome: identification of key features for a neonatal diagnosis

Abstract: Background: An early diagnosis of CHARGE syndrome is challenging, especially for the primary care physicians who often take care of neonates with multiple congenital anomalies. Here we report eight cases of CHARGE syndrome whose diagnosis was made early in life with the intent to identify the most helpful features allowing a prompt clinical diagnosis. Methods: Medical records of patients with CHARGE syndrome whose diagnosis was made at the Fondazione IRCCS Ca′ Granda Ospedale Maggiore Policlinico in Milan, Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is noteworthy, since about 95% of patients with CHD7 pathogenic missense variants have semicircular canal anomalies (Bergman et al 2012b ). Conversely, all four of our study subjects had bilateral EVA, whereas EVA has been reported to be present in only 10% of CHARGE patients, most frequently as unilateral EVA (Abadie et al 2000 ; Bedeschi et al 2020 ; Hoch et al 2017 ; Vesseur et al 2016 ). Although their temporal bone histopathology revealed an enlargement of the most proximal part of the endolymphatic duct, a recent report by da Costa et al concluded that none of six study subjects with CHARGE syndrome had EVA (da Costa Monsanto et al 2022 ).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is noteworthy, since about 95% of patients with CHD7 pathogenic missense variants have semicircular canal anomalies (Bergman et al 2012b ). Conversely, all four of our study subjects had bilateral EVA, whereas EVA has been reported to be present in only 10% of CHARGE patients, most frequently as unilateral EVA (Abadie et al 2000 ; Bedeschi et al 2020 ; Hoch et al 2017 ; Vesseur et al 2016 ). Although their temporal bone histopathology revealed an enlargement of the most proximal part of the endolymphatic duct, a recent report by da Costa et al concluded that none of six study subjects with CHARGE syndrome had EVA (da Costa Monsanto et al 2022 ).…”
Section: Discussionmentioning
confidence: 54%
“…Agenesis or hypoplasia of the semicircular canals is the most common malformation of the inner ear, identified in 95% of 35 patients with a CHD7 pathogenic variant (Bergman et al 2012b ). In contrast, unilateral or bilateral EVA has only been detected in a few patients with CHARGE syndrome (Abadie et al 2000 ; Bedeschi et al 2020 ; Hoch et al 2017 ; Vesseur et al 2016 ). Other signs of CHARGE include external ear anomalies, hypogonadotropic hypogonadism characterized by absent, partial or delayed puberty, anosmia or hyposmia, renal or collecting system malformations, cleft lip and/or cleft palate, cranial nerve dysfunction, and atopic disorders (Kong and Martin 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous pathogenic variants in CHD7 causes a wide spectrum of phenotype including CHARGE syndrome (OMIM #214800). CHARGE syndrome is an autosomal dominant multiple congenital anomaly syndrome that presents with variable constellations of the classic features of eye C oloboma, H eart defects, choanal A tresia, growth R etardation, G enitourinary anomalies, and E ar malformations, among other congenital anomalies and neurobehavioral problems (Bedeschi et al, 2020; Pagon et al, 1981). CHD7 is a chromodomain helicase‐DNA binding protein that plays a role in chromatin remodeling, and heterozygous pathogenic CHD7 variants are identified in most individuals clinically diagnosed with CHARGE syndrome (Janssen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ear abnormalities are frequent (> 90%) and are an important clinical clue for diagnosis in those cases with no additional major criteria [ 59 ]. Bedeschi MF et al [ 59 ] reported on eight patients with CHARGE syndrome and described external ear shape and position anomalies, middle ear ossicular malformations with chronic otitis media, and several inner ear anomalies cochlear and vestibular anomalies, consisting of varying degrees of cochlea hypoplasia and malformations and dysplasia of semi-circular canals. The authors outlined as middle and inner ear defects can be easier found by CT scan and MRI of the temporal bone, thus allowing a prompt clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%